Inflammation-responsive Drug-conjugated Dextran Nanoparticles Enhance Anti-inflammatory Drug Efficacy - Lee, Sangeun (ACS Appl Mater Interfaces, 2018)
Stimuli-responsive nanomaterials are especially interesting to enhance drug-delivery specificity for biomedical applications. With the aim to achieve a highly stable and inflammation specific drug release, we designed an reactive oxygen species (ROS)-responsive dextran-drug conjugate (Nap-Dex). By blending Nap-Dex with the acid-sensitive acetalated dextran polymer (Ac-Dex) we achieved a dual responsive nanoparticle with high specificity toward the inflammatory environment. The inflammatory environment not only has elevated ROS levels, but also a lower pH than healthy tissue, making pH and ROS highly suitable triggers to target inflammatory diseases. The anti-inflammatory COX-inhibitor naproxen was modified with an ROS-responsive phenylboronic acid and conjugated onto dextran. The dextran units were functionalized with up to 87% modified naproxen. This resulted in a complete drug release from the polymer within 20 min at 10 mM H(2)O(2). The dual responsive nanoparticles reduced levels of the pro inflammatory cytokine IL-6 120 times more efficiently, and TNFα 6 times more efficiently than free naproxen from lipopolysaccharide (LPS)-activated macrophages. These additional anti-inflammatory effects were found to be mainly attributed to ROS scavenging effects. In addition, the model cargo fluorescein diacetate was released in an LPS-induced inflammatory response in vitro. We believe that drug-conjugation using phenylboronic acid can be applied to various drugs and dextran based materials for enhanced drug-efficacy, where this work demonstrates the significance of functionalized carbohydrates polymer-drug conjugates.